The Influence of Organizational Support, Autonomy and Organizational Tenure on Affective Organizational Commitment - Faizatul Absharizan, Abu Bakar (2010)
This study was an assessment of the impact of the organizational support, autonomy, and organizational tenure in explaining affective organizational commitment among employees of Polytechnic Sultan Azlan Shah (PSAS). The purpose of this study was to investigate whether autonomy, organizational support and organizational tenure influence affective organizational commitment among the employees at PSAS. One interview with the with the Deputy of Director 1, PSAS was done before the study to assess problems the organization was facing and the outcome indicate some problem statement a mention in the problem statement section. A set of questionnaire consist of 28 question was distributed to 198 respondents from all departments. The numbers of sample need are derived from the Morgan Sampling Method. Statistical Package for Social Science (SPSS) version 16.0 was used to analyze the data and result from Pearson's Correlation Coefficient and regression analysis showed ,that only a organizational support and organizational tenure has a significant relationship with the affective organizational commitment.